Let's laugh - Locke, David Ross, 1833-1888.; Smith, Lloyd E. (Lloyd Edwin), 1902-1971. (Girard, Kan. : Haldeman-Julius Co., 1924)
A selection from various humorous newspaper letters.
Written pseudonymously by David Ross Locke.
Keywords: United States -- History -- Civil War, 1861-1865 -- Humor